Entidades fechadas de previdência complementar: protagonistas ou coadjuvantes nos desvios entre o direito de controle e do fluxo de caixa das empresas brasileiras - Cezar, Rafael dos Reis (2019)
Closed Supplementary Social Security Entities (CSSE) have become one of the most influential institutional investors in the various capital markets worldwide, especially in countries with weak legal protection of shareholders. In this context and in order to contribute to the lack of Brazilian literature on the issue, this work aims to analyze the impact of the control structure by the CSSE on the deviations between control rights and cash-flow rights in Brazilian publicly traded companies on B3 (Brazil, Bolsa [stock exchange], Balcão [Over-the-Counter Market]). The data refer to the period 1998 to 2017, totaling 866 observations. By using dynamic models of multiple linear regression estimated by GMM-Sys, the results showed that CSSE control structures affect positively and significantly the deviations between control rights and cash flows of the main shareholder as well as of the five largest shareholders. These results are consistent with studies by Doidge et al. (2009), who found evidence that controlling shareholders, mainly when control exceeds their participation in cash flows, tend to get private control benefits in detriment to the maximization of company value and in the emergence of the expropriation of minority shareholders. These effects have been possibly found because CSSE invest in the capital market for the sole purpose of diversifying portfolios and do not develop activist behaviors either because of lack of skills or because of monitoring costs that do not provide sufficiently compensatory returns in capital gains. It was also identified that CSSE control structure associated with the deviations between control rights and ownership of the main shareholder, three and five major shareholders positively impact the outsourcing of the votes trough consulting companies in general meetings.